The Comparison of S100 A8/A9 Protein Receptor Expression between Progressive and Non-Progressive Pterygium - Cerah Puspinarti; Elza Iskandar; Riani Erna; Wresnindyatsih Wresnindyatsih; Erial Bahar (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: S100 A8/A9 protein suggest have an activity at inflammation pathway caused fibroblast proliferation which is support the patofisiology teori of pterygium. Methods: This research is a cross sectional study consists of 21 subject who suffered primary nasal or temporal pterygium. All subject divided into 2 grup, progressive dan non progressive pterygium with this following criteria: length of pterygium at the cornea, diameter ilots de Fuch, thickness of corpus compare with apex dan hiperemia of pterygium. The tissue of pterygium after excised were examined through histopatology and immunohistochemical with HE and reagent Mab 27E10 staining to see S100 A8/A9 protein reseptor expression. And than we calculate between staining cell and intencity of the brown-colour of reseptor that call staining Index to see the trend to proggressive pterygium. Results: From 21 subject of study, amount of 11 subject (52,38%) progressive pterygium and 10 subject non progressive pterygium (47,62%). We found S100 A8/A9 protein reseptor expression at proggressive group were higher than non progressive group. Cut off point in staining index is 25 that show the pterygium has trend to be proggresive at that point or more. Histopatology examination there are strong correlation progresifity pterygium with squamous epithel prolifertion, cell inflamation, and vascular proliferation. Conclusion: There is a significant differentiate in S100 A8/A9 protein receptor expression between progressive and non progressive pterygium. Keywords: S100 A8/A9 protein, progressive pterygium, immunohistochemical